2010
DOI: 10.1016/j.jcrs.2010.06.067
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of corneal haze after collagen crosslinking for keratoconus and corneal ectasia: Scheimpflug and biomicroscopic analysis

Abstract: The time course of corneal haze after CXL was objectively quantified; it was greatest at 1 month, plateaued at 3 months, and was significantly decreased between 3 months and 12 months. Changes in haze did not correlate with postoperative clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
185
4
13

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(228 citation statements)
references
References 29 publications
20
185
4
13
Order By: Relevance
“…All adverse events were due to stromal haze formation, which induced a Effects and adverse events after CXL for keratoconus are independent of age PB Baenninger et al loss of BCVA, except for one case in a young patient where a contact lens-induced epithelial problem was the reason for vision deterioration at the 12-month followup. Taking into account that stromal haze formation is a common finding after CXL 15 and, because none of the patients experienced a severe complication, we still regard CXL as a relatively safe procedure in all age groups. A limitation of our study is that the failure rate (7.9-16.5%), defined as increase of K max Z1 Dpt after CXL, was somewhat higher than the failure rate reported in the literature (0-7.6%).…”
Section: Resultsmentioning
confidence: 99%
“…All adverse events were due to stromal haze formation, which induced a Effects and adverse events after CXL for keratoconus are independent of age PB Baenninger et al loss of BCVA, except for one case in a young patient where a contact lens-induced epithelial problem was the reason for vision deterioration at the 12-month followup. Taking into account that stromal haze formation is a common finding after CXL 15 and, because none of the patients experienced a severe complication, we still regard CXL as a relatively safe procedure in all age groups. A limitation of our study is that the failure rate (7.9-16.5%), defined as increase of K max Z1 Dpt after CXL, was somewhat higher than the failure rate reported in the literature (0-7.6%).…”
Section: Resultsmentioning
confidence: 99%
“…Crosslinking studies with long-term follow-up have shown that corneal thickness as well as central keratometry follows a dynamic curve over the first 6 months. 7,8 Although complete epithelial healing is achieved in the first few days postoperatively, epithelium remodeling is an acceptable explanation for the continuous changes seen over several months. Avoidance of contact lens corneal bearing and mechanical trauma to the center of the cornea seems to be crucial for undisrupted epithelium remodeling and normal corneal nerve proliferation after CXL.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggest that keratocyte apoptosis could be used as an indicator of CXL success. (44)(45) …”
Section: Safety Parameters and Potential Complicationsmentioning
confidence: 99%